Improving Participation and Learning Outcomes of SMP Students in Citizens Learning Materials of Independence Express Opinions Through The Application of Cooperative Model Type STAD With Lesson Study Pattern - Kasiana Kasiana (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
Abstract This study aims to increase the participation and understanding of students' citizenship education skills and to get better learning outcomes by applying the STAD-type cooperative learning model with a lesson study pattern. This type of research is a classroom action research involving 36 students of class VII.11 SMP Negeri 9 Kendari in the academic year 2021-2022. Data was collected using observation, tests, and questionnaires. Data were analyzed using descriptive methods. Based on the results of data analysis, the following results were obtained (1) the cooperative model of the STAD type with lesson study pattern had a positive impact on students' participation and understanding, (2) the learning process carried out could improve student learning outcomes, (3) improve students' ability to be more understand learning activities and the ability to apply problem-solving methods in all types of problems encountered and can feel the advantages of the STAD cooperative learning model with lesson study pattern, and (4) increase student participation/learning activities. Based on the results of this study, it is recommended to apply the STAD-type cooperative learning model with lesson study patterns in Civics or other subjects.